1998
DOI: 10.1038/sj.cdd.4400326
|View full text |Cite
|
Sign up to set email alerts
|

High frequency of persistent hyperplastic primary vitreous and cataracts in p53-deficient mice

Abstract: In order to investigate whether the p53 gene product plays a role in normal eye development, age matched p53-deficient mice and wild-type controls were sacrificed from day 2 to day 21 after birth. Eyes were paraffin-embedded and sectioned. Serial sections were taken at the level of the tunica vasculosa lentis and the hyaloid artery. The terminal dUTP nick-end labelling technique (TUNEL) was used to detect the number of cells displaying DNA fragmentation within these structures. Eyes were also prepared for scan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
45
1
1

Year Published

2001
2001
2014
2014

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(49 citation statements)
references
References 22 publications
2
45
1
1
Order By: Relevance
“…However, we occasionally observed several layers of retrolental cells in p53 Ϫ͞Ϫ eyes (Fig. 5b), a finding that is consistent with slowed or incomplete HVS regression in some mice (34,35). Importantly, we have not observed lens capsule disruption (Fig.…”
Section: Arf Is Expressed In the Vitreous Before Hyaloid Vascular Regmentioning
confidence: 58%
See 1 more Smart Citation
“…However, we occasionally observed several layers of retrolental cells in p53 Ϫ͞Ϫ eyes (Fig. 5b), a finding that is consistent with slowed or incomplete HVS regression in some mice (34,35). Importantly, we have not observed lens capsule disruption (Fig.…”
Section: Arf Is Expressed In the Vitreous Before Hyaloid Vascular Regmentioning
confidence: 58%
“…HVS regression involves apoptosis in endothelial cells (31,34) and pericytes (41). This apoptosis is at least partially p53-dependent because HVS regression is slowed or incomplete in inbred p53 Ϫ͞Ϫ BALB͞c (34) and C57BL͞6 (35) mice.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, it was demonstrated that retinal vascular development and neovascularization during oxygen-induced ischemic retinopathy is markedly attenuated in Bcl-2Ϫ/Ϫ mice (45). Pathological angiogenesis, such as the persistence of fetal ocular vasculature, can also be observed in mice deficient in proapoptotic proteins, Bax, Bak (22), and P53 (37). In light of this and other evidence, the inhibition of endothelial survival factors, or the activation of endothelial cell death machinery, is considered an attractive strategy in the inhibition of pathological angiogenesis, especially in clinical trials for cancer treatment (39).…”
Section: Discussionmentioning
confidence: 99%
“…36,39,50 All procedures on animals were approved by the local UCL Institute of Ophthalmology Ethics Committee and licensed by the United Kingdom Home Office. Animals were anaesthetised and pupillary mydriasis achieved as previously described.…”
Section: Intraocular Injectionsmentioning
confidence: 99%